Sex disparities in the prevalence of physical function disabilities: a population-based study in a low-income community - Orellano-Colón, Elsa M.; Suárez-Pérez, Erick L.; Rivero-Méndez, Marta; Boneu-Meléndez, Claudia X.; Varas-Díaz, Nelson; Lizama-Troncoso, Mauricio; Jiménez-Velázquez, Ivonne Z.; León-Astor, Arelí; Jutai, Jeffrey W. (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Functional disability continues to be a significant public health problem that increases older adults’ vulnerability to experience a diminished quality of life, loss of independence, higher healthcare costs and health services utilization, and increased risks of mortality. Thus, we aimed to study the prevalence of functional disabilities by sex according to the types of daily living activities, controlling for specific sociodemographic variables among older Hispanics from low-income communities. Methods We used a cross-sectional epidemiological research design, considering a complex sampling design of households to interview adults ≥65 years living in low-income communities in Puerto Rico. Functional disability was measured by the PROMIS® Physical Function Short Form-20 T-score. The selected community was reported to have 5980 adult residents ≥65 years, according to the USA Census. The prevalence of functional disability was estimated using the logistic regression model, weighting by the effect of the sampling. Our estimated prevalence was compared between sexes using the prevalence ratio (PR), which was estimated with logistic regression models, controlling for age, income, number of chronic conditions, high and low impact of chronic conditions in functional disabilities, marital status, and sampling design. Results We recruited 211 older Hispanics from a randomly selected sample. Their mean age was 74.4 ± 7.1 years, with female predominance (57.3%). The overall estimated prevalence of physical function disability using T-score among females was 2.70 (95% CI: 1.4, 5.1) times the estimated prevalence of physical function disability among males. Women were more likely to report functional disabilities in instrumental activities of daily living, self-care activities, and functional mobility compared to males. However, sex differences were largely explained by the presence of musculoskeletal conditions of high impact in functional disability. Conclusions The females in our study bear the greater burden of physical function disability in their adult age. Health policies, as well as future studies, should be targeted at reducing the burden of physical function disabilities in different types of daily activities through gender-sensitive disability self-management programs.